Proceedings of the 10th International Conference on Rotor Dynamics - IFToMM Vol. 3 - Cavalca, Katia Lucchesi; Weber, Hans Ingo.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
IFToMM conferences have a history of success due to the various advances achieved in the field of rotor dynamics over the past three decades. These meetings have since become a leading global event, bringing together specialists from industry and academia to promote the exchange of knowledge, ideas, and information on the latest developments in the dynamics of rotating machinery. The scope of the conference is broad, including e.g. active components and vibration control, balancing, bearings, condition monitoring, dynamic analysis and stability, wind turbines and generators, electromechanical interactions in rotor dynamics and turbochargers. The proceedings are divided into four volumes. This third volume covers the following main topics: dynamic analysis and stability; electromechanical interactions in rotordynamics; nonlinear phenomena in rotordynamics; rotordynamics of micro, nano and cryogenic machines; and fluid structure interactions in rotordynamics. .
Passive Control of the Critical Speeds of Rotating Shafts Using Eccentric Balancing Sleeves -- Application of Genetic Algorithm for Synthesis of H∞ Controllers for Active Magnetic Bearing Systems -- An Active Elastic Support/Dry Friction Damper ：New Modeling and Analysis for Vibration Control of Rotor Systems -- Identification of Crack and Internal Damping Parameters using Full Spectrum Responses from a Jeffcott Rotor Integrated with an Active Magnetic Bearing -- Robust Control Applied to Faulting Journal Bearing -- Control of Flexible Rotor Vibration With Flexibly Mounted Active Magnetic Bearings -- Reduction of Rotor Vibration a Amplitude Using PID Tuning Methods -- Experimental Validation of Angular Viscoelastic Dynamic Neutralizers Designed for Flexural Vibration Control in Rotating Machines -- Active Control of Rotating Machinery Under Rotor-stator Contact Conditions -- Applying Compressed Sensing to Blade Tip Timing Data: A Parametric Analysis.
Keywords: Machinery; Multibody systems; Vibration; Mechanics, Applied; Electric power production; Machinery and Machine Elements; Multibody Systems and Mechanical Vibrations; Electrical Power Engineering; Mechanical Power Engineering